Empowering application of basic life support management to cadre, District Astambul, Banjar Regency - Insana Maria; Annalia Wardhani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Cadres play a vital role in implementing health interventions within the community. Notably, 80 percent of emergency cases involving respiratory and cardiac arrest occur outside hospital settings. Cadres contribute significantly to building motivation and confidence in the management of Basic Life Support (BLS). This activity aimed to enhance the quality of health services by empowering community health cadres in BLS management. The method employed involved socialization and training provided to 22 community health cadres across villages in Astambul District. The results showed that 68 percent of cadres demonstrated a good level of knowledge following the socialization activities. The training outcomes indicated that 90 percent of cadres correctly performed the initial safety step ("scene safety") in BLS procedures. Overall, most cadres were able to perform BLS actions accurately, particularly in the stages of checking responsiveness, calling for help, and initiating recovery. It is recommended that follow-up efforts be made to further enhance cadres’ skills, especially in applying BLS as a means of developing community potential in the health sector.